2013
DOI: 10.1248/bpb.b12-00899
|View full text |Cite
|
Sign up to set email alerts
|

Alginate Enhances Excretion and Reduces Absorption of Strontium and Cesium in Rats

Abstract: Alginate (ALA), which is an intercellular polysaccharide associated with brown algae, is used as a food additive, a health food and a medicine. Here, we first examined the adsorption of strontium (Sr) and cesium (Cs) by ALA in vitro, and then evaluated the effects of ALA on absorption and excretion of Sr and Cs in rats, in order to evaluate its potential usefulness for minimizing radiation damage from materials released after a nuclear accident. Both Sr and Cs were concentration-dependently adsorbed by sodium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 8 publications
0
18
1
Order By: Relevance
“…20) Both additives increased the excretion of Sr, though Cs concentration was significantly reduced only in the Ca-Alg group. There have been some reports describing the capacity of Alg for metal binding and the order of affinity between Alg and metals.…”
Section: )mentioning
confidence: 90%
See 1 more Smart Citation
“…20) Both additives increased the excretion of Sr, though Cs concentration was significantly reduced only in the Ca-Alg group. There have been some reports describing the capacity of Alg for metal binding and the order of affinity between Alg and metals.…”
Section: )mentioning
confidence: 90%
“…Accordingly, the International Atomic Energy Agency (IAEA) has recommended Na-Alg intake for persons exposed to large amounts of radioactive Sr. 19) We have compared the effects of Na-Alg and Ca-Alg in promoting excretion and decreasing absorption of Sr and cesium (Cs) in rats. 20) Both additives increased the excretion of Sr, though Cs concentration was significantly reduced only in the Ca-Alg group. There have been some reports describing the capacity of Alg for metal binding and the order of affinity between Alg and metals.…”
mentioning
confidence: 90%
“…7,8) We have compared the effects of sodium alginate (Na-Alg) and calcium alginate (Ca-Alg) in promoting excretion and decreasing absorption of Sr and cesium (Cs) in rats. 9) Both additives increased the excretion of Sr, though Cs concentration was significantly reduced only in the Ca-Alg group. We also measured the plasma concentration of cholesterol in that study, and interestingly found that Ca-Alg has a greater cholesterol-lowering effect than Na-Alg.…”
mentioning
confidence: 90%
“…We also measured the plasma concentration of cholesterol in that study, and interestingly found that Ca-Alg has a greater cholesterol-lowering effect than Na-Alg. 9) At present, Na-Alg is widely used as a food additive (thickening agent) and as a health food to decrease blood cholesterol and inhibit weight gain. [10][11][12] However, sodium intake is associated with hypertension, 13) and Ca-Alg may be preferable to Na-Alg, if it has an equivalent pharmaceutical effect.…”
mentioning
confidence: 99%
“…Calcium alginate also carries plenty of carboxyl like TMS [27]. It has a great potential for the removal of strontium [28][29][30]. Carboxyl has strong binding forces with strontium and calcium.…”
Section: Effect Of Coexist Ionsmentioning
confidence: 99%